Editor's Choice-Prospective registry of cardiac critical illness in a modern tertiary care Cardiac Intensive Care Unit. Issue 8 (December 2019) - Watson, Ryan A; Bohula, Erin A; Gilliland, Thomas C; Sanchez, Pablo A; Berg, David D; Morrow, David A
Background: The changing landscape of care in the Cardiac Intensive Care Unit (CICU) has prompted efforts to redesign the structure and organization of advanced CICUs. Few studies have quantitatively characterized current demographics, diagnoses, and outcomes in the contemporary CICU. Methods: We evaluated patients in a prospective observational database, created to support quality improvement and clinical care redesign in an AHA Level 1 (advanced) CICU at Brigham and Women's Hospital, Boston, MA, USA. All consecutive patients ( N =2193) admitted from 1 January 2015 to 31 December 2017 were included at the time of admission to the CICU. Results: The median age was 65 years (43% >70 years) and 44% of patients were women. Non-cardiovascular comorbidities were common, including chronic kidney disease (27%), pulmonary disease (22%), and active cancer (13%). Only 7% of CICU admissions were primarily for an acute coronary syndrome, which was the seventh most common individual diagnosis. The top three reasons for admission to the CICU were shock/hypotension (26%), cardiopulmonary arrest (11%), or primary arrhythmia without arrest (9%). Respiratory failure was a primary or major secondary reason for triage to the CICU in 17%. In-hospital mortality was 17.6%. Conclusions: In a tertiary, academic, advanced CICU, patients are elderly with a high burden of non-cardiovascular comorbid conditions. Care has shifted from ACS toward predominantly shock and cardiac arrest, as well as non-ischemic conditions, and the mortality of these conditions is high. These data may be useful to guide cardiac critical care redesign.